Engineering ultrafast charge transfer in a bismuthene/perovskite nanohybrid. Issue 6 (30th January 2019) - Wang, Yingwei; Chen, Keqiang; Hao, Huang; Yu, Guannan; Zeng, Bowen; Wang, Hui; Zhang, Feng; Wu, Leiming; Li, Jianqing; Xiao, Si; He, Jun; Zhang, Yupeng; et al.
Abstract : 0-Dimensional (0D) CsPbBr3 QDs were integrated with 2D bismuthene to obtain a 0D/2D nanohybrid with tunable charge transfer efficiency. Abstract : In this work, 0-dimensional (0D) CsPbBr3 QDs were integrated with 2D bismuthene having ultrafast carrier mobility, to obtain a 0D/2D nanohybrid. Moreover, an excellent charge transfer efficiency (0.53) and an appreciable quenching constant of 2.3 × 10 5 M −1 were observed. Tuning the ratio of bismuthene in the Bi/perovskite nanohybrid achieved the quantified control of charge transfer efficiency and quenching performance at the interface.